2021
DOI: 10.1021/acsami.1c15609
|View full text |Cite
|
Sign up to set email alerts
|

PbS–Pb–CuxS Composites for Thermoelectric Application

Abstract: Composite materials offer numerous advantages in a wide range of applications, including thermoelectrics. Here, semiconductor−metal composites are produced by just blending nanoparticles of a sulfide semiconductor obtained in aqueous solution and at room temperature with a metallic Cu powder. The obtained blend is annealed in a reducing atmosphere and afterward consolidated into dense polycrystalline pellets through spark plasma sintering (SPS). We observe that, during the annealing process, the presence of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…With the optimized carrier density and mobility after Cu interstitial doping in PbS 0.6 Se 0.4 , the power factor undergoes a remarkable increase at wide temperature. The peak power factor increases from 3.88 μW cm −1 K −2 in PbS 0.6 Se 0.4 to 20.58 μW cm −1 K −2 in PbS 0.6 Se 0.4 − 1%Cu, as shown in Figure 3A, and the average power factor (PF ave ) in Supporting Information: Figure undergoes substantial increase, from 2.01 μW cm −1 K −2 in PbS 0.6 Se 0.4 to 18.38 μW cm −1 K −2 in PbS 0.6 Se 0.4 − 1%Cu at 300–773 K. Compared with other n ‐type PbS, including PbS–Cl–Sb, [ 39 ] PbS–In–Ga, [ 20 ] PbS–Te–Sn, [ 17 ] PbS–Se–Sb, [ 21 ] PbS–Pb–Cu x S [ 18 ] , and PbS–Se–Te–Ga, [ 22 ] PbS 0.6 Se 0.4 − 1%Cu in this study exhibits a superior power factor, as shown in Figure 3B, and also a highest PF ave at 300–773 K as seen in Supporting Information: Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the optimized carrier density and mobility after Cu interstitial doping in PbS 0.6 Se 0.4 , the power factor undergoes a remarkable increase at wide temperature. The peak power factor increases from 3.88 μW cm −1 K −2 in PbS 0.6 Se 0.4 to 20.58 μW cm −1 K −2 in PbS 0.6 Se 0.4 − 1%Cu, as shown in Figure 3A, and the average power factor (PF ave ) in Supporting Information: Figure undergoes substantial increase, from 2.01 μW cm −1 K −2 in PbS 0.6 Se 0.4 to 18.38 μW cm −1 K −2 in PbS 0.6 Se 0.4 − 1%Cu at 300–773 K. Compared with other n ‐type PbS, including PbS–Cl–Sb, [ 39 ] PbS–In–Ga, [ 20 ] PbS–Te–Sn, [ 17 ] PbS–Se–Sb, [ 21 ] PbS–Pb–Cu x S [ 18 ] , and PbS–Se–Te–Ga, [ 22 ] PbS 0.6 Se 0.4 − 1%Cu in this study exhibits a superior power factor, as shown in Figure 3B, and also a highest PF ave at 300–773 K as seen in Supporting Information: Figure .…”
Section: Resultsmentioning
confidence: 99%
“…(A) Thermal conductivity in PbS 0.6 Se 0.4 – x %Cu ( x = 0–2), and (B) comparison of lattice thermal conductivity between PbS 0.6 Se 0.4 – 1%Cu and previous works, including PbS–Cl–Sb, [ 39 ] PbS–In–Ga, [ 20 ] PbS–Te–Sn, [ 17 ] PbS–Se–Sb, [ 21 ] PbS–Pb–Cu x S, [ 18 ] and PbS–Se–Te–Ga. [ 22 ] …”
Section: Resultsmentioning
confidence: 99%
“…The SEM micrograph of the Yb 14 MnSb 11 /W composite and the homogeneous distribution of W nanoinclusions are shown in Figure a and b. Srivastava et al demonstrated that Fe nanoinclusions exhibit a higher α and lower σ than do Cu nanoinclusions in the SrTiO 3 -based composite because Fe has a lower σ than does Cu, as shown in Figure e and f. However, both Cu and Fe nanoinclusions enhance the total thermal conductivity of the composite due to the high thermal conductivity of both of the metals and still improve the overall ZT of the composites, as shown in Figure g and h. Li et al added Cu metallic nanoinclusions to the PbS matrix, Cu dissoluted and formed Pb domains, and Cu x S precipitates improved the ZT . The addition of Ag/Cu nanoparticles in the TE matrix material enormously improved the carrier concentration, employing spontaneous doping of the Ag/Cu atoms .…”
Section: Classification Of Nanoinclusionsmentioning
confidence: 97%
“…The size and shape of the metallic nanoinclusions affect the energy filtering effect . The composite’s enhanced κ is due to the electron thermal conductivity contribution from the metallic nanoinclusions. ,,, Metallic inclusions such as Cu, ,, Fe, , Zn, , B, Pt, Ag, ,,,, Bi, , Au, W, Si, ,, Sn, Ge, Yb, Te, and In , were used to improve the thermoelectric properties.…”
Section: Classification Of Nanoinclusionsmentioning
confidence: 99%
See 1 more Smart Citation